2019
DOI: 10.1088/1755-1315/269/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Variations of physicochemical properties of stingless bee honey from different botanical origin in state of Johor, Malaysia

Abstract: Physicochemical parameters analysis was used in the identification of varietal honey from different botanical origin. Botanical origin is one of the important parameter to be known as a quality control to meet the legislated mandatory requirement during commercialization. This study assessed the influence of the botanical origin on the physicochemical properties of stingless bee honey or known as kelulut honey in state of Johor, Malaysia. The honey samples were collected in six different botanical origins name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Melissopalynological studies on honey produced by nine species of stingless honey bees consisted of Cephalotrigona capitata, Melipona bicolor, M. marginata, M. mondury, M. quadrifasciata, M. scutellaris, M. seminigra, Scaptotrigona xanthotricha, and Tetragonisca angustula have been reported from Brazil (do Nascimento et al 2015). Similar study was for honey produced by Tetragonula iridipennis from India (Vijayakumar and Jeyaraaj 2016), honey of Tetragonula pagdeni from Thailand (Thakodee et al 2018), and honey produced by Heterotrigona itama from Malaysia (Majid et al 2019). However, publications on the diversity of pollen in honey produced by stingless bees from Lombok Island are still very limited.…”
Section: Introductionsupporting
confidence: 72%
“…Melissopalynological studies on honey produced by nine species of stingless honey bees consisted of Cephalotrigona capitata, Melipona bicolor, M. marginata, M. mondury, M. quadrifasciata, M. scutellaris, M. seminigra, Scaptotrigona xanthotricha, and Tetragonisca angustula have been reported from Brazil (do Nascimento et al 2015). Similar study was for honey produced by Tetragonula iridipennis from India (Vijayakumar and Jeyaraaj 2016), honey of Tetragonula pagdeni from Thailand (Thakodee et al 2018), and honey produced by Heterotrigona itama from Malaysia (Majid et al 2019). However, publications on the diversity of pollen in honey produced by stingless bees from Lombok Island are still very limited.…”
Section: Introductionsupporting
confidence: 72%
“…Basically, to evaluate honey's radical scavenging potential, the total phenolic and flavonoid contents are directly related to its antioxidant capacity [36]. Previous research showed the total content of phenolic and flavonoid of H. itama honey from different botanical origins in methanol extract ranged from 210.11 ± 0.11 to 413.94 ± 0.56 mg GAE/100 g and 179.36 ± 0.12 to 53.90 ± 1.30 mg RE/100 g, respectively [37]. ese figures are related to botanical sources, where the main pollen sample presents the highest phenolic and flavonoid content.…”
Section: Antioxidant Activitiesmentioning
confidence: 99%
“…The ash content of honey correlates to its mineral content and is influenced by the geographical, environmental, and botanical characteristics of the honey’s origin [ 44 ]. Stingless bee honey has been reported to possess higher ash content than Apis mellifera [ 13 , 14 , 21 , 45 , 46 ].…”
Section: Stingless Bee Honey Properties and Benefitsmentioning
confidence: 99%
“…This characteristic may also be affected by factors such as light exposure, heat, and duration of storage, as well as enzymatic reactions [ 20 , 49 ]. The darker-colored honey contains a higher quantity of total phenolics, indicating that it may have a high level of bioactivity [ 44 ].…”
Section: Stingless Bee Honey Properties and Benefitsmentioning
confidence: 99%